Formation of professional competencies of future physical education teachers - A.S. Kasmalieva, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the conditions and stages of formation of professionally significant technological competencies of bachelors of physical culture to improve the quality of training of future teachers of physical culture. Methods and structure of the study. The methods of generalization, systematization, methods of document analysis, generalization of the experience of pedagogical universities were used to specify the goals and objectives of the main educational program for the preparation of bachelors of physical culture in accordance with the requirements of the State Educational Standard of Higher Professional Education in the direction of "Physical Education" (2021) and the development of professional competencies of a physical education teacher in accordance with the stages of the learning process at the university. Results and conclusions. The content of the curricula for the training of bachelors of physical culture has been developed, in accordance with the requirements of the new State Standard of Higher Professional Education in the direction of "Physical Education" (2021), based on the principles of consistency, continuity, humanization of education, competence-based, personality-oriented and activity-based approaches to education. It was revealed that the use of a practice-oriented health-saving education trajectory contributes to the formation of professionally significant competencies of future physical education teachers.